2020
DOI: 10.3389/ftox.2020.586674
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving E-cigarette: Comparative Chemical Analyses of E-cigarette Vapor and Cigarette Smoke

Abstract: Background: E-cigarette designs, materials, and ingredients are continually evolving, with cotton wicks and diverse coil materials emerging as the popular components of atomisers. Another recent development is the use of nicotine salts in e-liquids to replicate the form of nicotine found in cigarette smoke, which may help cigarette smokers to transition to e-cigarettes. However, scientific understanding of the impact of such innovations on e-cigarette aerosol chemistry is limited.Methods: To address these know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Their designs have evolved from the first-generation devices (“cig-a-likes”) to devices with disposable, prefilled cartridges or “pods” and “mods” with user-controllable settings, such as wattage, voltage, and temperature control ( Zhu et al, 2014 ; Talih et al, 2017 ; FDA, 2019c ). ENDS products aerosolize the e-liquid that is typically composed of a mixture containing propylene glycol (PG), vegetable glycerol (VG), nicotine, and flavors ( Hahn et al, 2014 ; Flora et al, 2016 ; FDA, 2019c ; Cunningham et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their designs have evolved from the first-generation devices (“cig-a-likes”) to devices with disposable, prefilled cartridges or “pods” and “mods” with user-controllable settings, such as wattage, voltage, and temperature control ( Zhu et al, 2014 ; Talih et al, 2017 ; FDA, 2019c ). ENDS products aerosolize the e-liquid that is typically composed of a mixture containing propylene glycol (PG), vegetable glycerol (VG), nicotine, and flavors ( Hahn et al, 2014 ; Flora et al, 2016 ; FDA, 2019c ; Cunningham et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The US FDA has identified 92 harmful or potentially harmful constituents (HPHCs) in addition to nicotine (103) and public comment was recently sought on the proposal to add a further 19 compounds to the list (104). However, to our knowledge, only one study has investigated the emissions of these additional HPHCs (22). In practice, it has been suggested that Pre-Market Tobacco Product Applications should report at least 32 compounds (66).…”
Section: Chemical and Physical Characterizationmentioning
confidence: 99%
“…ECs generally do not reach temperatures higher than 250 °C during normal use or more than 350 °C under dry wicking conditions (105). However, a huge variety of devices and e-liquids exist (106) and many different puffing conditions and analytical techniques have been used to assess them (42,(107)(108)(109), but, overall, results indicate significantly lower levels of toxicants in EC aerosols than in cigarette smoke (20,22,43,44,102,110,111).…”
Section: Chemical and Physical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cigarette aerosol studies tend to use targeted HPHC analyses ( National Academies of Sciences, Engineering, and Medicine, Health and Medicine Division, Board on Population Health and Public Health Practice, Committee on the Review of the Health Effects of Electronic Nicotine Delivery Systems, 2018 ), such as, carbonyls ( Farsalinos and Gillman, 2018 ), metals ( Williams et al, 2013 ) and major e-liquid component thermal decomposition products ( Uchiyama et al, 2020 ). A few e-cigarette studies have targeted broader ranges of HPHC emissions, Lauterbach and Laugesen (2012), Tayyarah and Long 2014 , Cunningham et al (2020) with up to 150 measurands examined ( Margham et al, 2016 ). These studies have shown considerable differences between e-cigarette aerosols and cigarette smoke, detecting fewer HPHCs in e-cigarette aerosols, and lower concentrations of those that are present.…”
Section: Introductionmentioning
confidence: 99%